Amyloids in bladder cancer hijack cancer-related proteins and are positive correlated to tumor stage - Diego Alem; César X. García-Laviña; Francisco Garagorry; Dardo Centurión; Joaquina Farias; Hany Pazos-Espinosa; María Noel Cuitiño-Mendiberry; Carolina Villadóniga; Susana Castro-Sowinski; Martín Fló; Federico Carrión; Brenda Iglesias; et al. (Scientific Reports)
Abstract Despite the current diagnostic and therapeutic approaches to bladder cancer being widely accepted, there have been few significant advancements in this field over the past decades. This underscores the necessity for a paradigm shift in the approach to bladder cancer. The role of amyloids in cancer remains unclear despite their identification in several other pathologies. In this study, we present evidence of amyloids in bladder cancer, both in vitro and in vivo. In a murine model of bladder cancer, a positive correlation was observed between amyloids and tumor stage, indicating an association between amyloids and bladder cancer progression. Subsequently, the amyloid proteome of the RT4 non-invasive and HT1197 invasive bladder cancer cell lines was identified and included oncogenes, tumor suppressors, and highly expressed cancer-related proteins. It is proposed that amyloids function as structures that sequester key proteins. Therefore, amyloids should be considered in the study and diagnosis of bladder cancer.